Interpretation of Jae Hee Choi: Cadenza "Clarinet Concerto No. 3 in Bb – Allegro Moderato" by Carl Philip Stamitz - Supiarza, Hery; Annisa, Luli Angsal Lintang; Sarbeni, Irwan (Jurnal Seni Musik, 2023)
The research of Cadenza "Clarinet Concerto No. 3 in Bb – Allegro Moderato” by Carl Philipp Stamitz by Jae Hee Choi is motivated by the clarinet solo performance of a clarinetist performing the cadenza part of this concerto. The focus of this research is to find out the interpretation and technique of Jae Hee Choi's clarinet playing by analyzing the cadenza part through the interpretation and technique of playing the clarinet to be able to have a good impact in interpreting an interpretation of playing music, especially concertos in the baroque era. The method used in this research is a descriptive research method with three stages of analysis. The first stage is audio-visual analysis. The second stage rewrites the notation with the Sibelius application. The third step is to analyze the rewritten notes and make a comparison between the cadenza played by Jae Hee Choi and the original cadenza in this concerto. This research found two very important things namely; clarinet interpretation and technique. Interpretation includes interpretation of expression, rhythm, melody, and dynamics. The clarinet playing technique includes blowing techniques and fingering techniques.